Influencia de la defoliación de un hibrido varietal blanco de maíz (Zea mays L.) (1983)
The research was conducted during three semesters (1.97913, 1.98013 and I.981A) at the Experimental Station "Tulio Ospina", located in medium climate of Colombia (1.438 m.a.sJ. with 22°C of average temperature and 1.500 nun of annual rainfall). The objective of this research was to evaluate the effect of total and partial defoliation during the female flowering period upon grain yield, plant ear number, grain humidity, physiological maturity and grain filling period in the white semident experimental variety hybrid of corn Diacol V.351 x Cinimyt 307. The main conclusions were: I. The best contribution of dry matter to the grain came from leaves of the middle and upper third of the plant (almost 80 per cent of the total contribution). With extreme conditions of total defoliation during the silking period the stem contributed with 5 per cent of photosynthetic material to the graing flung. The dry grain weight and the ear number per plant decreased with total defoliation of the superior third, the middle third or the inferior and middle thirds of the plant or the whole and apparently it was not affected by the absence of the inferior leaves. The grain maturity was anticipated when the loss of the leaves was 66% or 100% and it was not affected with a 33% of defoliation, The grain filling took 76 days and it was reduced in 30 and 40 days when the defoliation was 66 and 100 per cent.